Analisa Teknomik Proses Pengelasan SMAW Menggunakan Elektroda Jenis E6013 Berbeda Merk Pada Material baja Grade A Marine use - bambang (Techno Bahari, 2021)
In the world of shipyard, especially steel ships, the welding process is absolutely necessary. To get maximum results, good and low economic value, a professional welder is needed, and the right type of electrode. The use of cheap electrodes to obtain economic value is often done by shipyards. Electrodes of the E6013 type are most often used in the affirmation process in shipyards, because of their low price. Analysis of the results of the SMAW method of welding joints using grade A marine use steel material using two electrodes with the type E6013 but different brands, is very necessary to make it easier for us to reach the most economical value and have stronger resistance. This study compared the butt joint welding of grade A marine use steel material with a thickness of 12 mm using the standard electrode E6013, XXbrand, with the Elektroda YYbrand, which then carried out tensile testing, bending testing and impact testing. The results of the test analysis on the two materials using XXhave a tensile strength of 466.92 MPa and fracture in the base material, no defects are found and have an energy of 134.72 Joules, at a price of Rp 19,000, - / kg, the welding process is less smoke. Whereas those who use Elektroda YYhave Tensile Strength 446.07 MPa and fractures in the base material, defects are found and have 130.72 Joule energy at a price of IDR 18,000 / kg, the welding process is a lot of smoke so that it also helt and safety from the welder.